Pemanfaatan Berbagai Jenis Limbah Rumput Laut terhadap Produktivitas Padi Sawah - Hariyati Hariyati; Bachrul Ibrahim; Asmita Ahmad (Jurnal Ecosolum, 2018)
Various ways have been made to increase the productivity of rice plants as a source of staple food of Indonesian society. One ofthem is the addition of nutrients in the soil (fertilization). Currently, the innovation use of seaweed as fertilizer is widely used in several countries in the world, because seaweed contains phosphorus, potassium, and some other micro elements. This study aimed to analyze the use of various types of waste seaweed to improve the productivity of paddy rice on the ground Vertisol. The study lasted from December 2014 through Sept. 2015, at Greenhouse, Teaching Farm, Faculty of Agriculture, University of Hasanuddin Makassar. The research method is a randomized block design consisting of eight treatments and six replications (48 pot experiment). Each treatment is C0 (control), C1 (fertilizer N 300 kg / ha, P 100 kg / ha and K 100 kg / ha), G1 (Gracilaria 10 g / pot), G2 (Gracilaria 100 g / pot), S1 (Sargassum 10 g / pot), S2 (Sargassum 100 g / pot), K1 (Kappaphycus 10 g / pot), and K2 (Kappaphycus 100 g / pot). The addition of Sargassum seaweed fertilizer waste 100 g / pot and Kappaphycus dose of 100 g / pot can increase K-dd, Na- dd, base saturation, increase the value of N, P, K, and Ca-dd, but administration with concentrations of 100 g / no maximum pot for rice crop production by causing toxicity in plants. The addition of seaweed fertilizer waste treatment Gracilaria 100 g / pot is effective in improving Vertisol soil chemical properties and can provide maximum results for the productivity of rice plants